Information Society's development in Peru - Yezerska, Lyudmyla (2022)
The last of the 20th century have been characterized by an accelerated process of technological advance. Internet's particular influence has contributed to rename our world: Information Society. Even though, its scarce penetration levels in Latin America, Africa and the Middle East, is seen as an obstacle. The present paper explores the development of Peru's Information Society, handing a state of the matter regarding information technologies in the country.